2018
DOI: 10.1073/pnas.1719880115
|View full text |Cite
|
Sign up to set email alerts
|

Population genomic analysis of elongated skulls reveals extensive female-biased immigration in Early Medieval Bavaria

Abstract: SignificanceMany modern European states trace their roots back to a period known as the Migration Period that spans from Late Antiquity to the early Middle Ages. We have conducted the first population-level analysis of people from this era, generating genomic data from 41 graves from archaeological sites in present-day Bavaria in southern Germany mostly dating to around 500 AD. While they are predominantly of northern/central European ancestry, we also find significant evidence for a nonlocal genetic provenanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 43 publications
9
69
0
Order By: Relevance
“…We collected published aDNA data from 1071 ancient individuals from Western Eurasia (west of 50° E), dated to between 38,000 and 1100 years before present (BP) (27, 29, 30, 3257). Using GWAS summary statistics for height from the UK Biobank (generated and made available by the Neale lab: http://nealelab.is/), we computed height PRS for each individual, using a P-value cutoff of 10 −6 , clumping variants in 250kb windows, and replacing missing genotypes with the mean across individuals (Methods).…”
Section: Resultsmentioning
confidence: 99%
“…We collected published aDNA data from 1071 ancient individuals from Western Eurasia (west of 50° E), dated to between 38,000 and 1100 years before present (BP) (27, 29, 30, 3257). Using GWAS summary statistics for height from the UK Biobank (generated and made available by the Neale lab: http://nealelab.is/), we computed height PRS for each individual, using a P-value cutoff of 10 −6 , clumping variants in 250kb windows, and replacing missing genotypes with the mean across individuals (Methods).…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to compare our neutral set of SNPs to another previously defined set of neutral regions of the human genome that has been used as a reference for demographic inferences in a series of studies (e.g. Gronau et al, 2011 ; McManus et al, 2015 ; King and Wakeley, 2016 ; Veeramah et al, 2018 ). Gronau et al (2011) have identified a set of 37,574 potentially neutral regions of 1 kb in length with carefully chosen properties (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…We finally retrieved 37,574 potentially neutral regions of 1 kb (e.g. Gronau et al, 2011 ; McManus et al, 2015 ; King and Wakeley, 2016 ; Veeramah et al, 2018 ) from http://compgen.cshl.edu/GPhoCS/data.php to make comparisons between our neutral set of SNPs to another possible sets.…”
Section: Methodsmentioning
confidence: 99%
“…Dependent on the analysis, target Migration Period samples were analyzed individually (to avoid the effects of relatedness) or together (using a set of unrelated individuals that maximized SNP number) Population Assignment Analysis. PAA was conducted as described in Veeramah et al 25 using the POPRES and HellBus datasets. Spatial Ancestry Analysis.…”
Section: Dna Isolation Screening Sequencing and Bioinformatic Procementioning
confidence: 99%